Advances in hemodialysis in the last decade in Latin America - María C. González-Bedat; Guillermo Rosa-Diez; Ricardo Correa-Rotter (Permanyer, 2023)
Kidney replacement therapy (KRT) initiated in Latin America towards the second half of the 20th century, starting with dialytic therapies and, shortly thereafter, with kidney transplant. By the end of 2021, close to half a million Latin Americans were under KRT, with an overall unadjusted prevalence of 872 per million persons (pmp), yet with significant heterogeneity between nations. By treatment modality, 68% of prevalent patients were treated with hemodialysis (HD), 9% with peritoneal dialysis (PD), and 23% were living with a functioning kidney graft (LFG). In the last decade, HD is the KRT that has had the largest growth, and it also has incorporated newer and better technologies. Nevertheless, Latin America shows heterogeneity between countries, and as a region we are far from achieving full accessibility to all in need of KRT. While there has been growth and improvement in existing renal dialysis registries, and several countries that did not previously have these registries have implemented them, there are still some nations with limited or absent registry implementation. The number of nephrologists in the region is heterogeneous, with only four countries having an appropriate group of specialists. The remaining nations have an important need to expand nephrology training programs. SLANH is a major regional player in addressing these topics and supporting the expansion of appropriate nephrology programs to improve inequalities and patient care.